Analisis Peran Tren Makeup Korean Look Sebagai Simbol Kecantikan Terhadap Persepsi Mahasiswa PKK - Mia Hafizah Tumangger; Taofan Ali Achmadi; Avis Nur Azimah; Keisha Najiha Aqila; Ratu Jauza Rinaldi; Najwa Diyan Evana Putri; Mellodya Nindyatera (Journal on Education, 2025)
The Korean Look makeup trend has become a popular symbol of beauty in various countries, particularly in Asia, including Indonesia. This study aims to analyze the role of the Korean Look makeup trend as a symbol of modern beauty in the perceptions of PKK students. Korean makeup styles, which emphasize a natural and feminine impression, are now widely adopted as a form of self-expression. The research method used a descriptive quantitative approach with 50 PKK student respondents using a Likert scale questionnaire (1–5) covering five main perceptual aspects. The results showed that students had a positive perception of the Korean Look 5. The most dominant aspect was the influence of social media (78%), while suitability with Indonesian facial characteristics showed mixed responses. In conclusion, the Korean Look has become a symbol of modern beauty influenced by popular culture and social media, but still needs to be adapted to local characteristics.